Effectiveness of Compassion-focused Group Therapy to Increase Self-compassion and Forgiveness in High School Students - Benu, Kristin Melliyati; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Jurnal Kajian Bimbingan dan Konseling, 2024)
Self-compassion and forgiveness are inseparable in the lives of adolescents because adolescents are vulnerable to various conflicts due to social changes and demands that cause negative emotions and other psychological problems. Adolescents need self-compassion and forgiveness to be able to regulate negative emotions in dealing with difficult situations. Compassion focused group therapy is an approach that focuses on compassion so that it can help adolescents to foster kindness to themselves, accept themselves and difficult situations as human and be able to provide forgiveness to themselves and others. This study aims to test the effectiveness of compassion-focused group therapy to increase self-compassion and forgiveness in students. This study used a pretest and multiple posttest research design. The research subjects consisted of 16 students of State Senior High School Giovanni, Kupang, Indonesia who were selected through purposive sampling. The research subjects were divided into experimental and control groups. The research instruments used were the compassion scale adapted from the SCS (self-compassion scale) into the Indonesian version and designed based on Kristin Neff's original work and the forgiveness scale designed by the author. The data obtained were analyzed using repeated measures mixed manova. The results of data analysis found that compassion-focused group therapy is effective for increasing self-compassion and forgiveness. Therefore, school counselors can apply compassion-focused group therapy to increase compassion and forgiveness in students. Future research is suggested to expand the research with different research designs and research subjects, analyze the effect of gender, age and cultural differences on the effectiveness of compassion-focused therapy and can test the effectiveness of compassion-focused therapy individually and its effectiveness on other dependent variables.